2018
DOI: 10.1007/s00330-018-5313-6
|View full text |Cite
|
Sign up to set email alerts
|

A noise-optimized virtual monoenergetic reconstruction algorithm improves the diagnostic accuracy of late hepatic arterial phase dual-energy CT for the detection of hypervascular liver lesions

Abstract: • Low-keV VMI+ are characterized by higher contrast resulting from maximum iodine attenuation. • VMI+ provides superior image quality compared with VMI or M_0.6. • 50-keV_VMI+ provides higher accuracy for the detection of hypervascular liver lesions < 1cm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 27 publications
4
35
0
Order By: Relevance
“…The objective image noise characteristics of MEI(+) reconstructions observed in this study are comparable with recent investigations that show increased noise for lower energy levels [ 5 , 10 , 17 ]. Interestingly, while subjective image parameters were best for MEI(+) reconstructions at 55 keV in the study by Frellesen, in our study, both readers favored the 40-keV and 50-keV MEI(+).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The objective image noise characteristics of MEI(+) reconstructions observed in this study are comparable with recent investigations that show increased noise for lower energy levels [ 5 , 10 , 17 ]. Interestingly, while subjective image parameters were best for MEI(+) reconstructions at 55 keV in the study by Frellesen, in our study, both readers favored the 40-keV and 50-keV MEI(+).…”
Section: Discussionsupporting
confidence: 90%
“…Several studies in the field of oncological and vascular imaging have shown that MEI(+) reconstructions are superior to MEI and PEI, providing excellent image quality due to significantly lower image noise at similar attenuation levels [ 5 , 8 – 10 , 15 18 ]. Only two of these studies investigated image quality in patients with PDAC [ 10 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, VM images provide reconstructions of specific kiloelectron volt (KeV). This allows for iodine contrast enhancement and artifact reduction reconstructions, which have been used in cardiac, pulmonary and abdominal vascular imaging [ 15 , 16 , 17 , 18 ], oncological imaging [ 19 , 20 , 21 ] and metal artifact reduction [ 22 , 23 ]. The second type of reconstructions are linked to material decomposition, i.e., differentiation of tissues based on atomic composition, which enables the separation of iodine contrast for VNC reconstructions [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%